2006
DOI: 10.1515/cclm.2006.108
|View full text |Cite
|
Sign up to set email alerts
|

Association of high-sensitive C-reactive protein with advanced stage β-cell dysfunction and insulin resistance in patients with type 2 diabetes mellitus

Abstract: Background: Type 2 diabetes mellitus is associated with increased cardiovascular risk. One laboratory marker for cardiovascular risk assessment is highsensitivity C-reactive protein (hsCRP). Methods: This cross-sectional study attempted to analyze the association of hsCRP levels with insulin resistance, b-cell dysfunction and macrovascular disease in 4270 non-insulin-treated patients with type 2 diabetes w2146 male, 2124 female; mean age "SD, 63.9"11.1 years; body mass index (BMI) 30.1"5.5 kg/m

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 32 publications
3
34
0
1
Order By: Relevance
“…Among inflammatory biomarkers, the best evidence to date supports the use of hs-CRP as an independent predictor of increased CVD risk in diabetic and non-diabetic patients. In addition, numerous clinical trials have established elevated CRP levels to be predictive of the development of insulin resistance, metabolic syndrome, and T2DM [7]. Our results are similar to another study [8] which reported that acute phase response was present in patients with type-2 diabetes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Among inflammatory biomarkers, the best evidence to date supports the use of hs-CRP as an independent predictor of increased CVD risk in diabetic and non-diabetic patients. In addition, numerous clinical trials have established elevated CRP levels to be predictive of the development of insulin resistance, metabolic syndrome, and T2DM [7]. Our results are similar to another study [8] which reported that acute phase response was present in patients with type-2 diabetes.…”
Section: Discussionsupporting
confidence: 89%
“…Large prospective studies pointed out the involvement of increased hs-CRP on cardiovascular morbidity and mortality in these patients. High levels of hs-CRP have been shown to be an independent predictor of cardiovascular risk for all degrees of severity of metabolic syndrome and T2DM [7], [9], and [10]. Regarding CIMT, there was a significant difference between patient groups and the control with mean CIMT in group I was 1.2±0.16, in group-II was 1.2±0.18 and in group-III was 0.5±0.1.…”
Section: Discussionmentioning
confidence: 97%
“…Results demonstrated that increased hs-CRP levels were linked to homeostatic model assessment, intact proinsulin, insulin, body mass index (BMI), and β-cell dysfunction (all p < 0.001) (Figure 3), but showed no correlation with disease duration or glucose control. 19 Another cross-sectional trial of participants in the Women's Health Study correlated hs-CRP with insulin resistance in nondiabetic women. The odds ratio for having elevated fasting insulin increased with each tertile of hs-CRP.…”
Section: High-sensitivity C-reactive Protein Correlates With Insulin mentioning
confidence: 99%
“…117,118 For example, CRP significantly inhibits cell proliferation and increases the rates of apoptotic cell death. 119 This effect was connected to the CRP-mediated modulation of protein kinase B (PKB), a key factor for cell survival pathways and to its ability to induce the production of TNF-α, IL-1β and matrix metalloproteinase-9 (MMP-9) in a concentration-dependent manner.…”
mentioning
confidence: 99%